2023
DOI: 10.1021/acs.langmuir.3c00703
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Wettability and Substrate Adherence of Thin Polymer Films with Surface-Segregating Bottlebrush Copolymer Additives

Abstract: We developed “reactive” bottlebrush polymers based on styrene (S) and t-butyl acrylate (tBA) as additives for polystyrene (PS) coatings. The bottlebrush polymers spontaneously bloom to both the air and substrate interfaces during solution casting. While neat PS films are hydrophobic and poorly adhere to the native oxide on clean silicon wafers, the hydrophilicity and substrate adherence of bottlebrush-incorporating PS films can be tailored through the thermally activated deprotection of tBA to produce acrylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Amphiphilic polymers provide a powerful and versatile platform for designing nanostructures suitable for a wide variety of applications, such as drug delivery, photonic crystals, , and stabilization of emulsions for food, , cosmetic , and oil recovery applications. Linear block copolymers have been widely studied as polymeric surfactants and emulsifiers due to their simple structure. However, it has been found that polymers with complex architectures, such as star and bottlebrush polymers, have interesting and enhanced interfacial properties. By using polyethylene oxide (PEO) star polymers, Li et al and Huang et al have shown that stable emulsions could be generated; they measured an interfacial tension reduction and an increased dilatational modulus induced by the presence of star polymers at the fluid interfaces. In a more recent work, Olszewski et al studied PEO stars with poly­(divinylbenzene) cores at air/water and oil/water interfaces and found that the interface was viscoelastic at high polymer concentration, and it became elastic as the concentration was reduced; these star polymers were also effective emulsion stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic polymers provide a powerful and versatile platform for designing nanostructures suitable for a wide variety of applications, such as drug delivery, photonic crystals, , and stabilization of emulsions for food, , cosmetic , and oil recovery applications. Linear block copolymers have been widely studied as polymeric surfactants and emulsifiers due to their simple structure. However, it has been found that polymers with complex architectures, such as star and bottlebrush polymers, have interesting and enhanced interfacial properties. By using polyethylene oxide (PEO) star polymers, Li et al and Huang et al have shown that stable emulsions could be generated; they measured an interfacial tension reduction and an increased dilatational modulus induced by the presence of star polymers at the fluid interfaces. In a more recent work, Olszewski et al studied PEO stars with poly­(divinylbenzene) cores at air/water and oil/water interfaces and found that the interface was viscoelastic at high polymer concentration, and it became elastic as the concentration was reduced; these star polymers were also effective emulsion stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, protection or deprotection changes the hydrophilicity of the molecule. Recently, it has been demonstrated that the deprotection of poly­( tert -butyl acrylate) can be used to tailor the wettability and adhesion property . A strong method to control the surface property is the fabrication of polymer brushes. Due to the covalent bonding to the substrate, the polymer brushes are fixed even when a soluble solvent is applied.…”
Section: Introductionmentioning
confidence: 99%